2012
DOI: 10.1167/iovs.11-9110
|View full text |Cite
|
Sign up to set email alerts
|

PDE4 Inhibition Suppresses IL-17–Associated Immunity in Dry Eye Disease

Abstract: Topical cilomilast suppresses the generation of IL-17-associated immunity in experimental DED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…Pathogenic CD4 cells that infiltrate the ocular surface tissues express receptors to these ligands (de Paiva et al, 2009; Yoon et al, 2007; Yoon et al, 2010; Dohlman TH et al, 2013). It has also been shown that manipulation of afferent (migration of dendritic cells from the ocular surface to the regional lymph nodes) or efferent (migration of differentiated CD4+ T cells from the nodes to the cornea and conjunctiva) can ameliorate development of dry eye disease (Coursey et al, 2012; Goyal et al, 2009; Lee et al, 2011; Sadrai et al, 2012; Schaumburg et al, 2011) indicating that therapeutic strategies that interfere with various points in this immune circle may have clinical significance. As a matter of fact, cyclosporine A 0.01 % emulsion, the only FDA-approved drug to treat dry-eye disease has been shown to modulate several arms of the immune response by decreasing human leukocyte class II antigen (HLA-DR) expression in conjunctiva of dry eye patients (Baudouin et al, 2002; Brignole et al, 2000; Brignole et al, 2001) and decreasing expression of IL-17A and IFN-γ in conjunctiva of animals after desiccating stress (de Paiva et al, 2009).…”
Section: 3 Th Cells In Dry Eyementioning
confidence: 99%
“…Pathogenic CD4 cells that infiltrate the ocular surface tissues express receptors to these ligands (de Paiva et al, 2009; Yoon et al, 2007; Yoon et al, 2010; Dohlman TH et al, 2013). It has also been shown that manipulation of afferent (migration of dendritic cells from the ocular surface to the regional lymph nodes) or efferent (migration of differentiated CD4+ T cells from the nodes to the cornea and conjunctiva) can ameliorate development of dry eye disease (Coursey et al, 2012; Goyal et al, 2009; Lee et al, 2011; Sadrai et al, 2012; Schaumburg et al, 2011) indicating that therapeutic strategies that interfere with various points in this immune circle may have clinical significance. As a matter of fact, cyclosporine A 0.01 % emulsion, the only FDA-approved drug to treat dry-eye disease has been shown to modulate several arms of the immune response by decreasing human leukocyte class II antigen (HLA-DR) expression in conjunctiva of dry eye patients (Baudouin et al, 2002; Brignole et al, 2000; Brignole et al, 2001) and decreasing expression of IL-17A and IFN-γ in conjunctiva of animals after desiccating stress (de Paiva et al, 2009).…”
Section: 3 Th Cells In Dry Eyementioning
confidence: 99%
“…6,20 Mice were housed in a low-humidity (relative humidity: <20%) controlled environment chamber (CEC) with constant air flow (15 L/min) for 12 days and received 5 mg/mL subcutaneous scopolamine hydrobromide (Sigma-Aldrich, St. Louis, MO) injections three times per day. Topical atropine sulfate (1%; Bausch & Lomb, Rochester, NY) was administered twice per day on days 1 and 2 to enhance anticholinergic effects.…”
Section: Dry Eye Modelmentioning
confidence: 99%
“…4 Antigen-presenting cells from the inflamed ocular surface home to the draining lymph nodes, where they prime naïve T cells to differentiate into pathogenic T effectors, including interleukin-17 secreting CD4þ T cells (Th17). These Th17 cells then migrate from the lymph nodes 5 to the conjunctiva, 6 where they propagate inflammation and cause tissue damage by secreting potent inflammatory cytokines. 7 Although several studies now implicate Th17 cells as the dominant pathogenic effectors in DED, 5,7,8 the specific mechanisms by which they migrate to the ocular surface are unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with phosphodiesterase type4 can reduce T H 17cellmediated ocular surface inflammation in an experimental animal model of dry eye. 88 To antagonize leukocyte trafficking, a small molecule inhibitor of LFA1 is being evaluated in dry eye in a phase III study. 89 Targeting signalling pathways is another promising strategy; for example, cytokine signal ling can be suppressed by Janus kinase (JAK) inhibitors.…”
Section: Therapeutic Approachesmentioning
confidence: 99%